Young age and adequate BCG are key factors for optimal BCG treatment efficacy in non-muscle-invasive bladder cancer - Liu, Kang; Nicoletti, Rossella; Zhao, Hongda; Chen, Xuan; Wu, Hongwei; Leung, Chi-Ho; D'Andrea, David; Laukhtina, Ekaterina; Soria, Francesco; Gallioli, Andrea; Wroclawski, Marcelo Langer; Castellani, Daniele; et al. (World journal of urology, 2024)
OBJECTIVE: To investigate the impact of ageing on survival outcomes in Bacillus Calmette-Guérin (BCG) treated non-muscle invasive bladder cancer (NMIBC) patients and its synergy with adequate BCG treatment. METHOD: Patients with NMIBC who received BCG treatment from 2001 to 2020 were divided into group 1 (< = 70 years) and group 2 (> 70 years). Overall Survival (OS), Cancer-Specific Survival (CSS), Recurrence-Free Survival (RFS), and Progression-Free Survival (PFS) were analyzed using the Kaplan-Meier method. Multivariable Cox regression analysis was used to adjust potential confounding factors and to estimate Hazard Ratio (HR) and 95% Confidence Interval (CI). Subgroup analysis was performed according to adequate versus inadequate BCG treatment. RESULTS: Overall, 2602 NMIBC patients were included: 1051 (40.4%) and 1551 (59.6%) in groups 1 and 2, respectively. At median follow-up of 11.0 years, group 1 (< = 70 years) was associated with better OS, CSS, and RFS, but not PFS as compared to group 2 (> 70 years). At subgroup analysis, patients in group 1 treated with adequate BCG showed better OS, CSS, RFS, and PFS as compared with inadequate BCG treatment in group 2, while patients in group 2 receiving adequate BCG treatment had 41% less progression than those treated with inadequate BCG from the same group. CONCLUSIONS: Being younger (< = 70 years) was associated with better OS, CSS, and RFS, but not PFS. Older patients (> 70 years) who received adequate BCG treatment had similar PFS as those younger with adequate BCG treatment.
Keywords: Cancer; Humans; Administration, Intravesical; lidé středního věku; Adjuvants, Immunologic; aplikace intravezikální; adjuvancia imunologická; Female; Aged; Free survival; věkové faktory; Neoplasm Invasiveness; výsledek terapie; senioři; lidé; Overall survival; nádory močového měchýře neinvadující svalovinu; Specific survival; Muscle; ženské pohlaví; Non-Muscle Invasive Bladder Neoplasms; Male; nádory močového měchýře; Middle Aged; Retrospective Studies; Treatment Outcome; Aged, 80 and over; BCG Vaccine; Recurrence; senioři nad 80 let; invazivní růst nádoru; retrospektivní studie; Age Factors; Age; míra přežití; BCG vakcína; mužské pohlaví; Non; Urinary Bladder Neoplasms; Progression; Invasive bladder cancer; Survival Rate